Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus Terhadap Tingkat Kemandirian Keuangan Daerah dan Dampaknya Terhadap Alokasi Belanja Modal (Studi Empiris Pada Pemerintah Kabupaten/Kota di Jawa Tengah) - Nabila, Farida Khansa, Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2017)
This research aim to analyse influence of local genuine revenues (PAD), public allocation fund (DAU) and special allocation fund (DAK) to local monetary independence storey and influence of PAD, DAU and DAK to capital expense allocation and also monetary independence to capital expense allocation at Government of Regency/Municipality in the Province of Central Java. This research used quantitative method by using report data realize APBD year 2014-2015 obtained Province of Central Java of formal website www.djpk.depkeu.go.id. Population and of sampel weared at this research are Regency/Municipality in Province of Central Java amounting to 35 Regency/Municipality spanned time of year 2014-2015. The data analyses used include test of normality, test autocorelation, test multicolinearity, test heteroskidastity, path analysis, coefficient of determinacy (Adjusted R2), test of F, and test of t. Pursuant to result of data analysis can be concluded that PAD and of DAU have an effect on to monetary independence, while DAK do not have an effect on to monetary independence. PAD have an effect on to capital expense allocation, while DAU and of DAK do not have an effect on to capital expense allocation. Monetary independence have an effect on to capital expense allocation. Test of F indicate that PAD, DAU, DAK and monetary independence have an effect on together (simultaneous) to capital expense allocation. Coefficient of determinacy test of Adjusted R2 showing the capital expense allocation influenced by PAD, DAU, DAK and monetary independence equal to 72,6%, and the model have got away from result of classical assumption.